Assessment of Environmental Variables as Potential Risk Factors for the Transmission of Leptospira spp. - Rosdi, Kira (Universiti Malaysia Sarawak (UNIMAS), 2020)
A diverse Leptospira serovars and reservoir hosts have been reported to circulate in various environmental settings in Sarawak. The risk of infection has been linked to socio-economic and environmental risk factors. This underscored the potential for a shift in the transmission dynamics of leptospirosis in Sarawak. It is imperative to consider the broad socio-demographical and environmental determinants such as climate and agricultural intensity, which may act as modifiable predictors for a disease like leptospirosis. These factors may be unevenly distributed, and their spatial distribution may influence the dynamics of leptospirosis. Hence, this study aims to determine the demographical and spatial distribution of leptospirosis using confirmed cases from 2011-2018 at a district level. This study also aims to investigate the global and localised relationship between leptospirosis with climate and agricultural variables. The demographical distribution of leptospirosis was analysed based on descriptive and inferential statistics by aggregating the data according to demographical groups. Spatial statistics including global and local Moran’s I was employed to study the spatial autocorrelation of leptospirosis incidence rate by districts. The potential clustering of hot spot and cold spot regions were investigated using Getis-Ord-Gi* statistics. The relationship between environmental factors and spatial density of geocoded leptospirosis cases was explored by using global Poisson regression (GPR) and geographically weighted Poisson regression (GWPR). A total of 4,648 cases were reported from 2011-2018 with the highest incidence in 2018, with 31 cases per 100,000 population. One hundred and thirty-nine fatal cases were reported, with the overall case fatality rate of 2.99%. Higher incidence rate per 100,000 population was observed in males (35.79; 95% CI: 22.92- 48.67), individuals aged between 50-59 years (27.22; 95% CI: 15.91- 38.53), other Bumiputera ethnic group (32.21; 95% CI: 16.80-47.82) and elementary occupational iv type (56.93; 95% CI: 26.49-87.37). Overall, the leptospirosis incidence in Sarawak demonstrated a positive spatial clustering (Moran’s I: 0.28) with significant positive local clustering observed in 2012 (Moran’s I: 0.23), 2013 (Moran’s I: 0.33) and the highest Moran’s I in 2014 (0.45). An increasing incidence trend was observed towards the southeast region with a standardised incidence ratio (SIR) between 0.39 and 4.54. The southeast region was identified as a significant hot spot region (z-scores: 1.58 to 2.83). Leptospirosis in the hot spot region was concentrated in areas with higher water vapour pressure (exp(β): 1.12; 95% CI: 1.02 - 1.25) and annual precipitation (exp(β): 1.15; 95% CI: 1.02 - 1.31), with lower precipitation in the driest month (exp(β): 0.85; 95% CI: 0.75 – 0.96) and the wettest quarter (exp(β): 0.88; 95% CI: 0.77 – 1.00). Water vapour pressure (WVP) has the most variation effect across the hot spot region with a standard deviation of 0.62 (LQ: 0.15; UQ; 0.99) while least variation in effect was observed in annual precipitation (ANNP) with a standard deviation of 0.14 (LQ: 0.11; UQ; 0.30). The GWPR model explained better relationships between leptospirosis and environmental covariates as denoted by the reduction in AICc value from 519.73 to 443.49. The results of localised relationships presented in this study could be used to formulate spatially targeted interventions. This would be useful particularly in localities with strong environmental or socio-demographical determinants for the transmission leptospirosis.